Designing Franchise System of Coffee Shop in Indonesia - Edrinal Sebayang, Toto; Saputra, Dony; Haw, Clara; Alicia, Alicia (International Journal of Engineering & Technology, 2018)
This research is motivated by development of new demands and lifestyle as an alternative opportunity for entrepreneurs in the field of coffee shop as franchise business. The purpose of this study is to analyze the business strategy of a coffee shop franchise as well as designing a franchise model of a coffee shop in Indonesia. The research method we use is quantitative descriptive method and case study approach. Data Collection method using interview to three coffee shop franchiseÂ owner, Data Analysis used are SWOT analysis, while model design using feasibility study. The result of this study is broad description of strength, weakness, opportunity and threats of coffee shop in Indonesia as well as a franchise model of coffee shop that can be implemented in IndonesiaÂ Â